European Energy Markets Observatory 2008 and Winter 2008/2009 Data Set Eleventh Edition, November 2009 - Lewiner, Colette. (Springer Netherlands, 2010)
Capgemini<U+0019>s European Energy Markets Observatory (EEMO) is an annual report that tracks the progress in establishing an open and competitive electricity and gas market in EU-27 (+ Norway and Switzerland) as well as the progress on the EU Climate-Energy package objectives. Launched in 2002 with the primary objective to assess the progress of deregulation in the European Member States, the report now tackles all the major issues faced by the Utilities industry. Through 70+ indicators, the report scans all the segments of the value chain and analyses the hot topics of the moment, to identify the key trends in the electricity and gas industries. The report includes country focus, highlighting the local key issues, and topic focus on leading-edge themes. Capgemini<U+0019>s partners <U+0013> Sociť ̌Gňřale Global Research and Strategy for their expertise in financial analysis, VaasaETT for their in-depth knowledge of customers<U+0019> behaviours and CMS Bureau Francis Lefebvre for their understanding of European energy policies and instances <U+0013> enrich the report on their respective area of expertise. The eleventh edition of the European Energy Markets Observatory covers the full year 2008 and the winter 2008/2009. Key messages developed in the report: -The crisis has put the Utilities sector under pressure and challenged the resilient character attributed to the Utilities sector. -Security of supply has improved in electricity, little progress was observed in gas. -Contrasted progress towards a single electricity and gas market. -Even if the European Union is the only region with a clear policy on climate change, more efforts need to be implemented. -The crisis has revealed the need for deeper Utilities business models changes: Utilities need to lower their <U+001c>cost to serve and distribution costs, adapt to new customer relationship, streamline and simplify their organizations, processes and IT to increase efficiency, manage their strategic resources and take advantage of new technologies.